2016
DOI: 10.1016/j.autrev.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease in adults: Observations in France and literature review

Abstract: Given the high frequency of cardiac involvement and complications in this series of AKD, diagnosis and treatment should not be delayed, and early IVIg treatment seems to improve the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 90 publications
(59 reference statements)
0
48
0
4
Order By: Relevance
“…The highest incidence is found in Japan; the most recent nationwide survey reported an incidence of 265/100,000 children under the age of 5 in 2012, and suggested that the incidence of KD is still rising [78]. Most patients are 6 months to 5 years old, although cases in older children and adults also occur [36]. The male/female ratio is approximately 1.5 to 1 [120].…”
Section: Epidemiologymentioning
confidence: 99%
“…The highest incidence is found in Japan; the most recent nationwide survey reported an incidence of 265/100,000 children under the age of 5 in 2012, and suggested that the incidence of KD is still rising [78]. Most patients are 6 months to 5 years old, although cases in older children and adults also occur [36]. The male/female ratio is approximately 1.5 to 1 [120].…”
Section: Epidemiologymentioning
confidence: 99%
“…Treatment with intravenous immunoglobulin reduces the risk of coronary aneurysms in childhood Kawasaki disease from 30% to 3% 7 . While Fraison and colleagues 5 found that early intravenous immunoglobulin treatment reduced the duration of fever, it did not significantly reduce the number of cardiac complications. A larger study assessing the role of intravenous immunoglobulin in adult‐onset Kawasaki disease is needed.…”
mentioning
confidence: 93%
“…The largest study of adult‐onset Kawasaki disease, by Fraison and colleagues, 5 reviewed 43 cases in France and found that, compared with childhood Kawasaki disease, adults are more likely to have liver function anomalies and arthralgias, and are less likely to have thrombocytosis, cheilitis and meningitis 3 , 5 . Coronary artery aneurysms are a devastating complication of this disease, and the rate of coronary complications in both adult‐onset and childhood Kawasaki disease is similar 5 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, frequency of clinical signs may vary between the two populations. [61] Although rare, adult onset KD is associated with high frequency of cardiovascular involvement. Because of its rarity and need to exclude other differential diagnoses, adult onset KD is usually diagnosed late.…”
Section: Introductionmentioning
confidence: 99%